Strain rate sensitivity of ultrafine grained aluminium alloy AA6061 - Vevecka-Priftaj, Aferdita; Böhner, Andreas; May, Johannes; Höppel, Heinz Werner; Göken, Mathias (4th International Conference on Nanomaterials by Severe Plastic Deformation, 2008)
The strain rate sensitivity of the aluminium alloy AA6061 has been investigated in a conventional grain sized (CG) state and in two different ultrafine grained (UFG) conditions processed by Equal Channel Angular Pressing (ECAP) for 2 and 6 passes at 100°C. Strain rate jump tests in compression were performed at different temperatures and the strain-rate sensitivity exponent m was determined. The tests were accomplished by microstructural investigations before and after compression testing in CG and UFG conditions. It is shown that all UFG microstructures exhibit strongly increased strain-rate sensitivity (SRS) compared to the CG state. The SRS increases with increasing temperature and is more pronounced for the UFG material processed using 6 ECAP passes. The microstructural investigations show a rather high stability of the grain structure for the UFG conditions up to 250°C. The results are discussed with respect to the relevant deformation mechanisms.
Created from Fastlane, Scopus look-up
Keywords: Equal channel angular pressing (ECAP); Severe plastic deformation; Strain rate sensitivity; Ultrafine-grained metals